P04 The phenotypic effects of antenatal multiple micronutrient supplementation in Nepalese children. (7th April 2014) - Devakumar, D; Wells, JCK; Chaube, SS; Saville, NM; Manandhar, DS; Costello, A; Ayres, JG; Stocks, J; Osrin, D
Abstract : Background: A growing body of evidence suggests that changes in early-life environment can have lasting effects. To investigate this, we followed up children from a double-blind randomised controlled trial of antenatal multiple micronutrient (UNIMAPP) supplementation. The trial showed the intervention group was 77 g heavier at birth and 204 g heavier at 2.5 years, with a 2.5 mmHg lower mean blood pressure. Aims: To investigate whether antenatal multiple micronutrient supplementation led to sustained phenotypic differences in mid-childhood. Methods: The study was conducted in the south of Nepal, from September 2011-December 2012. We measured anthropometry, body composition using bioelectrical impedance (with a population specific isotope calibration), blood pressure and kidney dimensions by ultrasound. Spirometry was performed according to the 'American Thoracic Society/European Respiratory Society' standards, adjusted for children. We produced a personal estimate of air pollution exposure by sampling respirable particle mass in the microenvironments in which the children reside. We calculated the crude difference by trial group, then constructed a directed acyclic graph from which we chose potential confounders in multiple linear regression models. Results: We saw 841 children (80% of total), mean age 8.5 years. Other than maternal education and residence, children lost to follow-up were no different. The unadjusted mean (95% CI) difference (intervention minus control), showed weight-for-age 0.05 z-scores (–0.09, 0.19), height-for-age 0.02 z-scores (–0.10, 0.15) and BMI-for-age 0.04 z-scores (–0.09, 0.18). Similarly there was no difference in blood pressure or lung function. The adjusted differences were similar for all outcomes. There was a tendency for girls in the intervention group to be slightly heavier with lower lung function values, but these results did not reach statistical significance. Conclusions: Differences in phenotype were not apparent at 8.5 years between children born to mothers who received antenatal UNIMMAP supplements compared with iron and folate. While not ruling out physiological differences and longer-term effects, our findings do not suggest a sustained effect of antenatal micronutrient supplementation on growth.